Clemastine Promotes Differentiation of Oligodendrocyte Progenitor Cells Through the Activation of ERK1/2 via Muscarinic Receptors After Spinal Cord Injury - Tong, Lu-Yao; Deng, Yong-Bing; Du, Wei-Hong; Zhou, Wen-Zhu; Liao, Xin-Yu; Jiang, Xue (Frontiers in Pharmacology, 2022)
The recovery of spinal cord injury (SCI) is closely associated with the obstruction of oligodendrocyte progenitor cells (OPCs) differentiation, which ultimately induces the inability to generate newly formed myelin. To address the concern, drug-based methods may be the most practical and feasible way, possibly applying to clinical therapies for patients with SCI. In our previous study, we found that clemastine treatment preserves myelin integrity, decreases the loss of axons and improves functional recovery in the SCI model. Clemastine acts as an antagonist of muscarinic acetylcholine receptor (muscarinic receptor, MR) identified from a string of antimuscarinic drugs that can enhance oligodendrocyte differentiation and myelin wrapping. However, the effects of clemastine on OPCs differentiation through MRs in SCI and the underlying mechanism remain unclear. To explore the possibility, a rat model of SCI was established.To investigate if clemastine could promote the differentiation of OPCs in SCI via MR, the expression of OPC and mature OL were detected at 7 days post injury (dpi) or 14 dpi. The significant effect of clemastine on encouraging OPC differentiation was revealed at 14 dpi rather than 7 dpi. Under pre-treatment with MR agonist cevimeline, the positive role of clemastine on OPCs differentiation was partially disrupted. Further studies indicated that clemastine increased the phosphorylation level of extracellular signal-regulated kinase 1/2 (p-ERK1/2) andthe expressions of transcription factors, Myrf and Olig2.To determine the relationship among clemastine, ERK1/2 signaling, specified transcription factors, and OPCs differentiation, the ERK1/2 signaling was disturbed by U1026. The inhibition of ERK1/2 in SCI rats treated with clemastine decreased the expressions of p-ERK 1/2, Myrf, Olig2 and mature OLs, suggesting that ERK1/2 is required for clemastine on promoting OPCs differentiation and that specified transcription factors may be affected by the activity of ERK1/2. Moreover, the impact of clemastine on modulating the level of p-ERK 1/2 was restricted following cevimeline pre-injecting, which provides further evidence that the role of clemastine was mediated by MR.Altogether,our data demonstrated that clemastine,mediated by MRs, promotes the OPCs differentiation under the positive role of Myrf and Olig2 through activating ERK1/2 signaling, and suggests a novel therapeutic prospect for SCI recovery.